Chapter 1
1.1 Describing a Set
Set: A set is a collection of objects.
Notation: Let \(A\) be a set. If \(a\) is an element of \(A\), we write \(a \in A\). Otherwise, \(a \notin A\).
The Empty Set: The empty set \(\emptyset\) contains no elements.
Describing a set
- Explicit list: \(S = \{ 1, 2, 3 \}\)
- By a property: \(S = \{ x \in \mathbb{U} : p(x) \}\)
- Read: all \(x\) in the universal set \(\mathbb{U}\) such that \(x\) satisfies some property \(p\). \[ \begin{align} S &= \{ x \in \mathbb{R} : x^2 + x - 1 = 0 \}\\ T &= \{ x \in \mathbb{Z} : \left|{x - 2}\right| = 5 \} \end{align} \]
Notation: \(|S|\) is the cardinality of, or number of elements in, \(S\).
\[ \begin{align} |\emptyset| &= 0\\ \left|\{ 1, \{ \emptyset, 15 \} \}\right| &= 2 \end{align} \]
Special Sets
- \(\mathbb{N}\): Naturals
- \(\mathbb{R}\): Reals
- \(\mathbb{Q}\): Rationals
- \(\mathbb{Z}\): Integers
1.2 Subsets
Subset: \(A\) is a subset of \(B\), written \(A \subseteq B \), means every element of \(A\) is also an element of \(B\).
Notation: \(C \nsubseteq D\) means there is an element of \(C\) which does not lie in \(D\).
Note: Let \(A\) be a set.
\[\emptyset \subseteq A\]
Familiar sets in \(\mathbb{R}\), intervals: Nine types:
- \((a, b) = \{ x \in \mathbb{R} : a < x < b \}\)
- \((a, b] = \{ x \in \mathbb{R} : a < x \leq b \}\)
- \(\vdots\) (fill in the rest)
Note: \((a, b) \neq \{ a, b \}\)
Equality: What does \(A = B\) mean?
\[ A \subseteq B, B \subseteq A \]
Venn Diagrams are useful set visualizations!
Proper Subset: \(A\) is a proper subset if \(A \subseteq B\) and \(A \neq B\), written \(A \subset B\).
Power Set: Given a set \(A\), the set of all subsets of \(A\) is called the power set of \(A\).
\[ \text{power set}(A) = \mathbb{P}(A) \]
Example: \(A = \{ a, b \}\) \[ \mathbb{P}(A) = \{ \emptyset, \{ a \}, \{ b \}, \{ a, b \} \} \] Observe: \[ |\mathbb{P}(A)| = 2^{|A|} \]
Fact: If \(A\) is a finite set, then \(\mathbb{P}(A) = 2^{|A|}\). (we will prove this later)
1.3 Set Operations
Note: All sets here are subsets of some universal set \(\mathbb{U}\).
Intersection: \(A \cap B = \{ x \in \mathbb{U}: x \in A \text{ and } x \in B \}\)
- Disjoint: If \(A \cap B = \emptyset\), we say \(A, B\) are disjoint.
Union: \(A \cup B = \{ x \in \mathbb{U}: x \in A \text{ or } x \in B \}\)
Difference: \(A \backslash B = \{ x \in \mathbb{U}: x \in A \text{ and } x \notin B \}\)
Complement of \(A\): \(\overline{A} = \mathbb{U} \backslash A = \{ x \in \mathbb{U}: x \notin A \}\)
\(A \backslash B = A \cap \overline{B}\)
Warning! \(\overline{\mathbb{N}}\): what is the universal set \(\mathbb{U}\)?
1.4 Indexed Collections of Sets
Given many sets: \[ A_1, A_2, \dots, A_n \quad n \text{ sets, } n \in \mathbb{N} \]
Union: \[ \begin{align} A_1 \cup A_2 \cup \dots \cup A_n &= \bigcup_{i=1}^n{A_i}\\ &= \{ x \in \mathbb{U}: x \in A_i \text{ for some } i, i=1\dots n \} \end{align} \]
Intersection: \[A_1 \cap A_2 \cap \dots \cap A_n = \bigcap_{i=1}^n{A_i}\]
Example:
For \(n \in \mathbb{N}, S_n = \{ n, 2n \}\). Suppose \(I = \{ 1, 2, 4 \}.\)
\[
\text{Find }\bigcup_{\alpha \in I}{S_\alpha}
\]
\[ \bigcup_{\alpha \in I}{S_\alpha} = \bigcup_{\alpha \in \{ 1, 2, 4 \}}{S_\alpha} = S_1 \cup S_2 \cup S_3 \] \[ = \{ 1, 2 \} \cup \{ 2, 4 \} \cup \{ 4, 8 \} = \{ 1, 2, 4, 8 \} \]
1.5 Partitions of Sets
Pairwise Disjoint: Let \(A\) be a set. A collection \(S\) of subsets of \(A\) is pairwise disjoint if every two distinct sets in \(S\) are disjoint.
Partition: Let \(A\) be a set. If \(S\) is a collection of non-empty subsets of \(A\) and
- \(S\) is pairwise disjoint and
- the union of the subsets in \(S\) is \(A\)
then we say \(S\) is a partition of \(A\).
This can be useful if, for example, we're trying to prove a theorem for the integers \(Z\). If we can prove the theorem for each partition, for example the positives, negatives, and zero separately, then we prove for the whole set \(Z\).
1.6 Cartesian Products of Sets
Cartesian Product of A and B: Let \(A, B\) be sets.
\[ A \times B \overset{def} = \{ (x, y): x \in A, y \in B \} \]
In general, \(A \times B \neq B \times A\).
Chapter 2
Statements
Statement:
- A declarative sentence or assertion.
- Either true or false.
- NOT both true and false.
So, every statement has a truth value \(T\) (true) or \(F\) (false).
Notation:
- \(P, Q, R, \dots\)
- \(P_1, P_2, P_3, \dots\) Remember, these are sentences!
Open Sentence: An open sentence is one whose truth value depends on one or more variables [placeholders].
Notation: \(P(x), Q(x), \dots\)
Negations
not P
~ P
Disjunctions & Conjunctions
Disjunction: or
Conjunction: and
Implications
Often referred to as a conditional statement.
- If \(P\), then \(Q\).
- \(P\) implies \(Q\).
- \(P \Rightarrow Q\)
Idea: A true statement cannot imply a false statement.
More on Implications
Recall: \(P \implies Q\) is a statement built from statements.
Now: \(P(x) \implies Q(x)\) is a statement built from open sentences. This is the form of most theorems.
Example:
\[ \begin{align} P(x)&: x = -3\\ Q(x)&: |x| = 3 \end{align}\\ \text{If } x = -3, \text{ then } |x| = 3. \]
Biconditionals
Converse: The implication \(Q \implies P\) is called the converse of the implication \(P \implies Q\).
- True for open sentences too!
Note!
Note!
\(P \implies Q\) and \(P \implies Q\) have no logical connection!
The Double Implication (biconditional)
\[ P \iff Q \overset{def}{=} (P \implies Q) \ \wedge (Q \implies P) \]
We say:
- \(P \iff Q\)
- \(P\) is equivalent to \(Q\)
- \(P\) if and only if \(Q\)
- \(P\) iff \(Q\)
- Older: \(P\) is necessary and sufficient for \(Q\)
Whenever you're given an English phrasing for double implication, immediately replace it by \(\iff\) and proceed from there.
IMPORTANT: \(P \iff Q = T\) for \(P, Q = (T, T)\) OR \(P, Q = (F, F)\)
Tautologies and Contradictions
Compound Statement: A compound statement is a statement composed of
- one or more component statements
- at least one logical connective \([\text{~}, \wedge, \vee, \implies, \iff]\)
Tautology: A compound statement is called a tautology if it is always true for all possible combinations of truth values of its component statements.
Contradiction: A compound statement is called a contradiction if it is always false for all possible combinations of truth values of its component statements.
Logical Equivalence
Logical Equivalence: If two compound statements have the same truth values for all combinations of their component statements, then we say they are logically equivalent/
The text uses the symbol \(\equiv\), but we'll use \(\iff\) in this course.
Theorem 2.17
If \(P, Q\) aare statements (or open sentences), then
\[ \begin{gather} P \implies Q\\ \iff\\ (\neg{P}) \vee Q \end{gather} \]
Proof:
\(P\) | \(Q\) | \(P \implies Q\) | \((\neg{P}) \vee Q\) |
---|---|---|---|
T | T | T | T |
T | F | F | F |
F | T | T | T |
F | F | T | T |
Fundamental Properties of Logical Equivalence
Theorem 2.18 - Fundamental Logical Equivalences
-
- \((P \vee Q) \iff (Q \vee P)\)
- \((P \wedge Q) \iff (Q \wedge P)\)
-
- \(P \vee (Q \vee R) \iff (P \vee Q) \vee R\)
- \(P \wedge (Q \wedge R) \iff (P \wedge Q) \wedge R\)
-
- \(P \vee (Q \wedge R) \iff (P \vee Q) \wedge (P \vee R)\)
- \(P \wedge (Q \vee R) \iff (P \wedge Q) \vee (P \wedge R)\)
-
- \(\neg{(P \vee Q)} \iff (\neg{P}) \wedge (\neg{Q})\)
- \(\neg{(P \wedge Q)} \iff (\neg{P}) \vee (\neg{Q})\)
Example: Write negations of the following open sentences:
- internet was unstable during lecture, couldn't get these copied down. should be in recording from September 1st!
Quantified Statements
missed intro because of bad internet
- For all/every/each \(x \in S, P(x)\) is written \(\forall x \in S, P(x)\)
- universal quantifier
- There exists/is/for some/at least one/ \(x \in S\) such that \(P(x)\)
- \(\exists x \in S, P(x)\)
- existential quantifier
\[ ~[\exists x \in \mathbb{R}: x^2=3] \iff \forall x \in \mathbb{R}: x^2 \neq 3 \]
Characterizations
Chapter 3
Trivial and Vacuous Proofs
Theorem: A true mathematical statement is called a
- theorem
- proposition, result, fact
- (everyday usage)
- lemma
- (helper theorem)
- corollary
- (follows immediately)
We usually consider
\[ P(x) \implies Q(x) \]
- where the variable(s) \(x \in \mathbb{S}\), universal set
Observations:
- \(P(x) \implies Q(x)\) is True if it is true for all \(x \in \mathbb{S}\)
- \(P(x) \implies Q(x)\) is False if it is false for at least one \(x \in \mathbb{S}\).
Next, recall:
\(P(x)\) | \(Q(x)\) | \(P(x) \implies Q(x)\) |
---|---|---|
T | T | T |
T | F | F |
F | T | T |
F | F | T |
- Observe: If \(Q(x)\) (the conclusion) is always True, then \(P(x) \implies Q(x)\) (the implication) is True.
- Called: A trivial proof (the hypothesis is irrelevant)
Example:
- Let \(x \in \mathbb{R}\).
- If \(x < 0\), then \(x^2+1 > 0\).
- Observe: \(\forall x \in \mathbb{R}\), we have \(x^2 \geq 0\).
- So \(x^2+1 \geq 0 +1 > 0\)
- Meaning the conclusion is always true.
- So, this result is trivially true.
Example:
- Observe: If \(P(x)\) (the hypothesis) is always false, then \(P(x) \implies Q(x)\) is true.
- Called: A vacuous proof (the conclusion is irrelevant)
Example:
- \(x \in \mathbb{R}\). If \(x^2 - 2x + 2 \leq 0\) then \(x^3 \geq 8\).
- Proof:
- Observe \(\forall x \in \mathbb{R}\), we have
- \(x^2 - 2x + 2 = (x^2 - 2x + (-1)^2) + 2\)
- \(= (x-1)^2 + 1 \geq 0 + 1\)
- \(> 0\)
- Meaning the hypothesis is always false.
- So this result is vacuously true.
- Observe \(\forall x \in \mathbb{R}\), we have
Recall the classic fact: For all sets \(A, \emptyset \subseteq A\). We can now prove this!
- If \(x \in \emptyset\), then \(x \in A\).
- Note that \(x \in \emptyset\) is always false.
- Therefore, this statement is vacuously true!
Direct Proofs
Direct Proof: In a direct proof of \(P(x) \implies Q(x)\) we consider an arbitrary element \(x\) for which \(P(x)\) is true and logically deduce that, for this \(x, Q(x)\) is also true.
Familiar Integer Facts We Assume
- the negation of an integer is an integer
- the sum, difference, or product of integers is an integer.
Even: An integer \(n\) is even if \(n=2k\) for some \(k \in \mathbb{Z}\)
Odd: An integer \(n\) is odd if \(n=2k+1\) for some \(k \in \mathbb{Z}\)
Result 3.4: If \(n\) is an odd integer, then \(3n+7\) is an even integer.
Proof:
- Assume \(n\) is an odd integer.
- So \(n = 2k+1, k \in \mathbb{Z}\).
- We want to show that \(3n+1 = 2a, where a \in \mathbb{Z}\)
- Observe (look!): \[ \begin{align} 3n+7 &= 3(2k+1)+7\\ &= 6k+10\\ &= 2(3k+5)\\ \end{align} \]
- Noting that \(3k+5 \in \mathbb{Z}\), 3n+7 is even. \(\blacksquare\)
General Steps
- Begin with the hypotehsis
- Deduce what you can from the hypothesis
- State your goal/conclusion
- PROVE the goal!
- Be guided by the upcoming conclusion
- End with the conclusion.
Result 3.6: If \(n\) is an odd integer, then \(4n^3+2n-1\) is odd.
Proof:
- Assume \(n\) is an odd integer.
- So \(n = 2y+1, y \in \mathbb{Z}\).
- We want to show that \(4n^3+2n-1 = 2a + 1, a \in \mathbb{Z}\).
- Observe:
\[ \begin{align} 4n^3 + 2n - 1 &= 4(2y+1)^3+2(2y+1)-1\\ &= 2\left[2(2y+1)^3+(2y+1) - 1\right] + 1 \end{align} \]
- Thus, \(4n^3+2n-1\) is odd. \(\blacksquare\)
Proof by Contrapositive
Contrapositive: The contrapositive of \(P(x) \implies Q(x)\) is the implication \(\neg Q(x) \implies \neg P(x)\)
Fact: \(P(x) \implies Q(x) \iff \left[ \neg Q(x) \implies \neg P(x)\right]\)
Proof:
\(P(x)\) | \(Q(x)\) | \(\neg P(x)\) | \(\neg Q(x)\) | \(P(x) \implies Q(x)\) | \(\neg Q(x) \implies \neg P(x)\) |
---|---|---|---|---|---|
T | T | F | F | T | T |
T | F | F | T | F | F |
F | T | T | F | T | T |
F | F | T | T | T | T |
This results in a proof technique called proof by contrapositive.
Result 3.10: let \(x \in \mathbb{Z}\). If \(5x-7\) is even, then \(x\) is odd.
Proof (Contrapositive):
- Assume \(x\) is even, so \(x = 2k, k \in \mathbb{Z}\).
- We want to show that given \(x\) is even, then \(5x-7\) is odd (\(5x-7 = 2n+1, n \in \mathbb{Z}\)).
- Observe: \[ \begin{align} 5x-7 &= 5(2k)-7\\ &= 2(5k)-8 + 1\\ &= 2(5k-4) + 1 \end{align} \]
- So, \(5x-7\) is odd. \(\blacksquare\)
The contrapositive is often used when the hypothesis is difficult, but the conclusion is relatively simple.
Words of Conclusion
So, thus, therefore, hence, whence, thence, then, it follows that, we have, ...
Result: let \(x \in \mathbb{Z}\). \[ x -7 \text{ is even} \iff x \text{ is odd.} \]
Proof:
- Assume \(x\) is odd. Then \(x = 2k+1, k \in \mathbb{Z}\).
- We want to show that \(11x-7 = 2a, a \in \mathbb{Z}\).
- Observe: \[ \begin{align} 11x - 7 &= 11(2k+1) - 7\\ &= 2(11k+11) + 11 - 7\\ &= 2(11k) + 4\\ &= 2(11k+2)\\ \end{align} \]
- So \(11x-7\) is even.
For the forward direction, we'll prove by contrapositive.
- Assume \(x\) is even, so \(x = 2k, k \in \mathbb{Z}\).
- We want to show that \(11x-7 = 2a+1, a \in \mathbb{Z}\).
- Observe: \[ \begin{align} 11x-7 &= 11(2k)-7\\ &= 2(11k) - 8 + 1\\ &= 2(11k-4)+1 \end{align} \]
- So, \(11x-7\) is odd. \(\blacksquare\)
Theorem 3.12
- Let \(x \in \mathbb{Z}\). \(x^2\) is even \(\iff x\) is even.
Proof
- Assume \(x\) is even. In other words, \(x = 2k, k \in \mathbb{Z}\).
- We want to show that \(x^2 = 2a, a \in \mathbb{Z}\).
- Observe: \[ x^2 = (2k)^2 = 2(2k^2) \]
- We'll prove the forward direction by contrapositive.
- Assume \(x\) is odd. In other words, \(x = 2k+1, k \in \mathbb{Z}\).
- We want to show that \(x^2 = 2a + 1, a \in \mathbb{Z}\).
- Observe: \[ \begin{align} x^2 &= (2k+1)^2\\ &= 4k^2+4k+1\\ &= 2(2k^2+2k)+1 \end{align} \]
- So, \(x^2\) is odd. \(\blacksquare\)
What about \(x^2\) is odd \(\iff x\) is odd? We just proved that too!
Result to prove: let \(x \in \mathbb{Z}\). If \(5x-7\) is odd, then \(9x+2\) is even.
- Neither a direct proof nor a contrapositive proof seems useful, or at least neither seem like a clean approach.
- Technique: Introduce a lemma.
- A lemma helps bridge the gap between hypothesis and conclusion.
- A lemma is a separate result on its own!
Lemma: let \(x \in \mathbb{Z}\).
- if \(5x-7\) is odd, then \(x\) is even. (invented hypothesis to simplify)
- We'll prove by contrapositive.
- Assume \(x\) is odd, so \(x = 2k+1, k \in \mathbb{Z}\).
- We want to show that \(5x-7 = 2a, a \in \mathbb{Z}\).
- Observe: \[ \begin{align} 5x-7 &= 5(2k+1) - 7\\ &= 2(5k)+5 - 7\\ &= 2(5k) - 2\\ &= 2(5k-1) \end{align} \]
- So, \(5x-7\) is even. \(\blacksquare\)
Result 3.14: let \(x \in \mathbb{Z}\).
- If \(5x-7\) is odd, then \(9x+2\) is even.
Proof: Assume \(5x-7\) is odd. By the above lemma, \(x\) is even.
- So \(x = 2k, k \in \mathbb{Z}\).
- We want to show that \(9x+2 = 2a, a \in \mathbb{Z}\).
- Observe:
\[ \begin{align} 9x + 2 &= 9(2k)+2\\ &= 2(9k+1) \end{align} \]
- So, \(9x+2\) is even. \(\blacksquare\)
Proof by Cases
Proof by Cases: In proving a mathematical statement \(P(x) \implies Q(x)\) where \(x \in \mathbb{S}\), sometimes \(x\) has more than one dijoint property. It may be helpful to separately prove \(P(x) \implies Q(x)\) for each different property of \(x\). This is called Proof by Cases.
Examples:
- For \(n \in \mathbb{Z}\), \(n\) is even or \(n\) is odd.
- For \(x, y \in \mathbb{R}, x \neq 0, y \neq 0\), \(xy > 0\) or \(xy < 0\).
- alternatively..
- \((x > 0 \text{ and } y > 0)\) or \((x < 0 \text{ and } y < 0)\) or \((x > 0 \text{ and } y < 0)\) or \((x < 0 \text{ and } y > 0)\)
Result 3.15: If \(n \in \mathbb{Z}\), then \(n^2 + 3n+5\) is odd.
Proof: Assume \(n \in \mathbb{Z}\).
- Notice that \(n\) can only be even or odd. If we prove the theorem for both cases, we've proven the theorem generally. Let the conclusion guide you!
- The parity of \(n\) is relevant only because the parity of an expression depending on \(n\) is relevant.
- Case 1: \(n\) is even, so \(n = 2k, k \in \mathbb{Z}\).
\[
\begin{align}
n^2 + 3n + 5 &= (2k)^2+3(2k)+4+1\\
&= 2(2k^2+3k+2)+1
\end{align}
\]
- So \(n^2+3n+5\) is odd.
- Case 2: \(n\) is odd, so \(n = 2k+1, k \in \mathbb{Z}\).
\[
\begin{align}
n^2 + 3n + 5 &= (2k+1)^2+3(2k+1)+5\\
&= 4k^2 + 4k + 1 + 6k + 3 + 5\\
&= 4k^2 + 10k + 9\\
&= 2(2k^2 + 5k + 4) + 1
\end{align}
\]
- So \(n^2+3n+5\) is odd. \(\blacksquare\)
An even-ness - oddness tale:
Parity: Let \(x, y \in \mathbb{Z}\). \(x\) and \(y\) are of the same parity if both are even or both are odd. Otherwise, \(x\) and \(y\) are of opposite parity.
Theorem 3.16: let \(x, y \in \mathbb{Z}\). \(x\) and \(y\) are of the same parity \(\iff x+y\) is even.
- If you're trying to prove a theorem based on \(x\) and \(y\) and it doesn't matter which is which, this is referred to as the theorem being symmetric in \(x\) and \(y\). This means we can swap \(x\) and \(y\) and the conclusion doesn't change. We refer to this as "Without Loss of Generality", or "WLOG".
Theorem 3.17: let \(a, b \in \mathbb{Z}\). \(ab\) is even \(\iff a\) even or \(b\) even.
- Backwards: Assume \(a\) is even or \(b\) is even.
- We want to show that \(ab = 2a, a \in \mathbb{Z}\).
- WLOG, assume \(a\) is even.
- So \(a = 2k, k \in \mathbb{Z}\).
- Observe: \(ab = (2k)b = 2(kb)\).
- So \(ab\) is even.
- Forwards (by contrapositive): Assume \(a\) is odd and \(b\) is odd.
- \(a = 2k+1, b=2j+1, k, j \in \mathbb{Z}\).
- Observe: \[ \begin{align} ab &= (2k+1)(2j+1)\\ &= 4kj + 2k + 2j + 1\\ &= 2(2kj+k+j)+1 \end{align} \]
- So \(ab\) is odd. \(\blacksquare\)
Proof Evaluations
Chapter 4
Proofs Involving Divisibility of Integers
Divides: if \(a, b \in \mathbb{Z}\) with \(a \neq 0\), we say "\(a\) divides \(b\)" if \(\exists c \in \mathbb{Z}: b = ac\).
-
We write \(a \mid b\).
-
We also say:
- \(b\) is a multiple of \(a\).
- \(a\) is a divisor of \(b\).
-
If \(a\) does not divide \(b\), we write \(a \nmid b\).
-
Old: \(ab\) even \(\iff a\) is even or \(b\) is even.
-
New: \(2 \mid ab \iff 2 \mid a \vee 2 \mid b\)
Result 4.1: let \(a, b, c \in \mathbb{Z}\) with \(a \neq 0\) and \(b \neq 0\).
- If \(a \mid b\) and \(b \mid c\), then \(a \mid c\).
- Proof:
- Assume \(a \mid b\) and \(b \mid c\).
- Then \(b = ax\) and \(c = by\), \(x, y \in \mathbb{Z}\).
- We want to show that \(a \mid c\), meaning \(c = a \cdot \square, \square \in \mathbb{Z}\).
- Observe:
\[ \begin{align} c = by = (ax)y = a(xy) \end{align} \]
- So \(a \mid c\). \(\blacksquare\)
Result 4.3: let \(a, b, c, x, y \in \mathbb{Z}\), where \(a \neq 0\).
- If \(a \mid b\) and \(a \mid c\), then \(a \mid (bx + cy)\).
- Proof:
- Assume \(a \mid b\) and \(a \mid c\), \(a \neq 0\).
- Wrong: Then \(b = ax\) and \(c = ay, x, y \in \mathbb{Z}\).
- We've already used \(x\) and \(y!\)
- Then \(b = ar\) and \(c = as, r, s \in \mathbb{Z}\).
- We want to show that \(a \mid (bx+cy\) meaning \(bx+cy = a \cdot \square, \square \in \mathbb{Z}\).
- Observe:
\[ \begin{align} bx + cy &= (ar)x+(as)y\\ &= a(rx+sy) \end{align} \]
- So \(a \mid (bx+cy)\). \(\blacksquare\)
Result 4.4: let \(x \in \mathbb{Z}\). If \(2 \mid (x-1)\), then \(4 \mid (x-1)\).
- Proof:
- Assume \(2 \mid (x^2-1)\).
- So \(x^2 - 1 = 2y, y \in \mathbb{Z}\).
- We want to show that \(4 \mid (x^2-1)\), meaning \(x^2-1 = 4 \cdot square, \square \in \mathbb{Z}\).
- It's not clear what to do here!
- That indicates that we probably need to try another path.
- Try isolating the x term: \(x^2 = 2y+1\).
- Notice: \(2y+1\) is odd, and we have a theorem saying that \(r^2\) odd \(\iff r\) odd!
- This means \(x\) is odd.
- So \(x = 2u+1, u \in \mathbb{Z}\).
- Observe:
\[ \begin{align} x^2 - 1 &= (2u+1)^2-1\\ &= 4u^2+4u+1-1\\ &= 4(u^2+u) \end{align} \]
- So \(4 \mid (x^2-1)\). \(\blacksquare\)
Result 4.5: Let \(x, y \in \mathbb{Z}\). If \(3 \nmid xy\), then \(3 \nmid x\) and \(3 \nmid y\).
- Proof by Contrapositive
- Assume \(~(3 \nmid x)\) and \(\neg 3\nmid y\)
- \(3 \mid x\) or \(3 \mid y\).
- So \(x = 3s\) or \(y = 3t\), \(s, t \in \mathbb{Z}\).
- We want to show that \(3 \mid xy\), meaning \(xy = 3\square, \square \in \mathbb{Z}\).
- WLOG, assume \(3\mid x\), meaning \(x = 3s\).
- Observe: \(xy = (3s)y = 3(sy)\).
- So \(3 \mid xy\).
- Assume \(~(3 \nmid x)\) and \(\neg 3\nmid y\)
Handy Observations: let \(n \in \mathbb{Z}\).
- \(n = 2q\) or \(n = 2q+1\), \(q \in \mathbb{Z}\).
- \(n = 3q\) or \(n = 3q+1\) or \(n = 3q+2\), \(q \in \mathbb{Z}\).
- For multiples of 2, we have 2 sets. Multiples of 3, 3 sets. Multiples of 4?
- Notice the pattern :)
Result 4.6 let \(x \in \mathbb{Z}\).
- If \(3 \nmid (x^2-1)\), then \(3 \mid x\).
- Proof by Contrapositive:
- Assume \(3 \nmid x\).
- So \(x\) is not a multiple of 3.
- So by the handy observation, \(x = 3q+1\) or \(x = 3q+2\), \(q \in \mathbb{Z}\).
- We want to show that \(3 \mid (x^2-1)\), meaning \(x^2-1 = 3\square, \square \in \mathbb{Z}\).
- Case 1: \(x = 3q+1\)
\[
\begin{align}
x^2-1 &= (3q+1)^2 - 1\\
&= 9q^2+6q+1-1\\
&= 3(3q^2+2q)
\end{align}
\]
- So \(3 \mid (x^2 - 1)\).
- Case 2: \(x = 3q+2\).
\[
\begin{align}
x^2 - 1 &= (3q+2)^2\\
&= 9q^2 + 12q + 4 - 1\\
&= 9q^2 + 12q + 3\\
= 3(3q^2+4q+1)
\end{align}
\]
- So \(3 \mid (x^2-1)\).
- Case 1: \(x = 3q+1\)
\[
\begin{align}
x^2-1 &= (3q+1)^2 - 1\\
&= 9q^2+6q+1-1\\
&= 3(3q^2+2q)
\end{align}
\]
Proofs Involving Congruence of Integers
Motivation
Let \(x, y \in \mathbb{Z}\).
- \(n = 2\): \(x, y\) must have the form \(2q\) or \(2q+1, q \in \mathbb{Z}\).
- Observe: \(x - y = \{2a-2b, (2a+1) - (2b+1)\} = 2(a-b)\).
- \(n = 3\): \(x, y\) must have the form \(3q, 3q+1, 3q+2, q \in \mathbb{Z}\).
- Observe: \(x - y = \{3a-3b, (3a+1)-(3b+1), (3a+2)-(3b+2)\} = 3(a-b)\).
For \(a, b, n \in \mathbb{Z}, n \geq 2\), we say \(a\) is congruent to \(b \pmod n\) written \(a \equiv b \pmod n\)
- "\(a\) equals \(b\) \(\pm\) a multiple of \(n\)"
- means \(n \mid (a-b)\).
New Interpretation: \(x \in \mathbb{Z}\).
- \(x = 2q\) or \(x = 2q+1, q \in \mathbb{Z}\).
- \(x \equiv 0 \pmod 2\) or \(x \equiv 1 \pmod 2\).
Result 4.9: let \(a, b, k, n \in \mathbb{Z}, n \geq 2\).
- If \(a \equiv b \pmod n\), then \(ka \equiv kb \pmod n\).
- Proof:
- Assume \(a \equiv b \pmod n\).
- This means \(n \mid (a - b)\).
- Hence \(a - b = nx, x \in \mathbb{Z}\).
- We want to show that \(ka \equiv kb \pmod n\), meaning \(n \mid (ka - kb)\)
- hence \(ka - kb = n\square, \square \in \mathbb{Z}\).
- Observe:
\[ \begin{align} ka - kb &= k(a - b)\\ &= k(nx)\\ &= n(kx) \end{align} \]
- Thus \(ka \equiv kb \pmod n\). \(\blacksquare\)
Result 4.10: let \(a, b, c, d, n \in \mathbb{Z}, n \geq 2\).
- If \(a \equiv b \pmod n\) and \(c \equiv d \pmod n\)
- Then \(a + c \equiv b + d \pmod n\)
- Proof:
- Assume \(a \equiv b \pmod n\) and \(c \equiv d \pmod n\).
- meaning \(n \mid (a-b)\) and \(n \mid (c-d)\)
- Hence \(a - b = nx\) and \(c - d = ny, x, y \in \mathbb{Z}\)
- We want to show that \(a + c \equiv b+d \pmod n\), meaning \(n \mid \left[(a+c)-(b+d)\right]\)
- Observe:
- Assume \(a \equiv b \pmod n\) and \(c \equiv d \pmod n\).
\[ \begin{align} (a + c) - (b + d) &= (a - b) + (c - d)\\ &= nx + ny\\ &= n(x + y) \end{align} \]
- So \(a + c \equiv b + d \pmod n\)
Result 4.11: let \(a, b, c, d, n \in \mathbb{Z}, n \geq 2\).
- If \(a \equiv b \pmod n\) and \(c \equiv d \pmod n\)
- Then \(ac \equiv bd \pmod n\).
- Proof: Assume \(a \equiv b \pmod n\) and \(c \equiv d \pmod n\).
- So, \(a - b = nx\) and \(c - d = ny, x, y \in \mathbb{Z}\).
- We want to show that \(ac \equiv bd \pmod n\), so \(ac-bd = n\square, \square \in \mathbb{Z}\).
- we have \(a = b+nx\) and \(c = d+ny\)
- Observe:
\[ \begin{align} ac-bd &= (b+nx)(d+ny)-bd\\ &= bd+bny + nxd + nxny - bd\\ &= n(by+xd+xny) \end{align} \]
- So \(ac \equiv bd \pmod n\). \(\blacksquare\)
Result 4.12: let \(n \in \mathbb{Z}\).
- If \(n^2 \not\equiv n \pmod 3\)
- then \(n \not\equiv 0 \pmod 3\) and \(n \not\equiv 1 \pmod 3\)
- For equals:
- \(n^2 \neq n \implies [n \neq 0 \wedge n \neq 1]\) means \([n = 0\) or \(n = 1] \implies n^2=n\)
- For equals:
- Proof by Contrapositive
- Assume \(\neg[n \not\equiv 0 \pmod 3]\) and \(n \not\equiv 1 \pmod 3\).
- \(n \equiv 0 \pmod 3\) OR \(n \equiv 1 \pmod 3\).
- We want to show that \(n^2 \equiv n \pmod 3\), so \(n^2 - n = 3\square, \square \in \mathbb{Z}\).
- Case 1: \(n \equiv 0 \pmod 3\)
- So \(n - 0 = 3k, k \in \mathbb{Z}\).
- Observe: \(n^2 - n = (3k)^2-(3k) = 3(3k^2-k)\).
- So \(n^2 \equiv n \pmod 3\).
- Case 2: \(n \equiv 1 \pmod 3\).
- So \(n - 1 = 3j, j \in \mathbb{Z}\).
- \(n = 1+3j\).
- Observe: \[ \begin{align} n^2-n &= (1+3j)^2 - (1+3j)\\ &= 1 + 6j + 9j^2 - 1 -3j\\ &= 3(2j+3j^2-j) \end{align} \]
- So \(n^2 \equiv n \pmod 3\).
- So \(n - 1 = 3j, j \in \mathbb{Z}\).
- Assume \(\neg[n \not\equiv 0 \pmod 3]\) and \(n \not\equiv 1 \pmod 3\).
Proofs Involving Real Numbers
Facts
- \(a^2 \geq 0, \forall a \in \mathbb{R}\)
- \(a^n \geq 0, \forall a \in \mathbb{R}\) if \(n \in \mathbb{Z}\) is even.
- \(a^n < 0, \forall a < 0\) if \(n \in \mathbb{Z}\) is odd.
- \([ab > 0] \iff a > 0\) INCOMPLETE
Let \(a, b, c \in \mathbb{R}\).
- \(a \geq b\), divide by \(c \geq 0\)
- \(ac \geq bc\)
- \(a \geq b\), divide by \(c > 0\)
- \(\tfrac{a}{c} \geq \tfrac{b}{c}\).
- \(a > b\), multiply or divide by \(c > 0\)
- \(ac > bc\)
- \(\tfrac{a}{c} > \tfrac{b}{c}\)
- \(a > b\), multiply or divide by \(c < 0\)
- \(ac < bc\)
- \(\tfrac{a}{c} < \tfrac{b}{c}\)
Theorem 4.13 (Zero Product Rule)
-
Let \(x, y \in \mathbb{R}\).
-
If \(xy = 0\), then \(x = 0\) or \(y = 0\).
- Note: this provides a "proof technique"
- If a product of reals is 0, then one of those reals must be 0.
- Note: this provides a "proof technique"
-
Proof: Assume \(xy = 0\).
- WLOG, consider \(x\).
- Case 1: \(x = 0\): Done :)
- Case 2: \(x \neq 0\).
- So \(\tfrac{1}{x}\) is defined.
- Observe: \[ \begin{align} xy &= 0\\ \tfrac{1}{x}(xy) &= \tfrac{1}{x}(0)\\ y &= 0 \quad \blacksquare \end{align} \]
-
Alternate Proof (Contrapositive)
- Assume \(\neg(x = 0 \vee y = 0)\)
- So \(x \neq 0 \wedge y \neq 0\)
- From here, solve by cases (\(x > 0, y > 0\), etc)
- Assume \(\neg(x = 0 \vee y = 0)\)
Result 4.14: Let \(x \in \mathbb{R}\).
- If \(x^3-5x^2+3x = 15\), then \(x = 5\).
- Proof: Assume \(x^3 - 5x^2 + 3x = 15\).
\[ \begin{align} x^3 - 5x^2 + 3x - 15 &= 0\\ x^2(x-5) + 3(x-5) &= 0\\ (x^2+3)(x-5) &= 0\\ \end{align} \]
- By the Zero Product Rule, either \(x^2+3 = 0\) or \(x-5 = 0\).
- \(x^2+3 = 0 \implies x^2=-3\) (contradiction)
- \(x - 5 = 0 \implies x=5\) \(\blacksquare\)